Investigation of a large-scale P2P VoD overlay network by measurements - Li, Bing (2013)
The proliferation of large-scale Peer-to-Peer (P2P) Video on Demand (VoD) overlays has created the demands to characterize and to understand the emergent properties of P2P VoD applications. In this paper, we investigate the P2P VoD overlay network, spanned by PPLive application, using active measurements. We have developed a piece of measurement software, named as VoDCrawler, to implement the experiment. Different from other existing work, our study focuses on the topology and the churn of the overlay networks. From the study, we have revealed the major features of the P2P VoD overlay networks and have compared them with those in P2P file sharing and live streaming systems. The discoveries we have obtained could help further investigation of the operation of the P2P VoD systems and favor the commercial developments of the P2P VoD applications.